Peningkatan Pemahaman Konsep Ipa Menggunakan Media Ubur-Ubur Pintar Melalui Metode Game Based Learning Di Mts - Sofi Asiyah (Jurnal Pendidikan dan Ilmu Fisika, 2025)
The objectives of this study are: 1) to determine the improvement in students' understanding of concepts, and 2) to assess the level of students' understanding of concepts in the application of smart jellyfish media. This study uses a quantitative approach with an experimental research type and a quasi-experimental design. The research employs a non-equivalent control group design. The data analysis techniques used include item analysis with validity and reliability tests, preliminary data analysis with normality and homogeneity tests, hypothesis testing with an independent sample t-test, and advanced analysis using the N-gain test. The results of the study show that: 1) there was a significant improvement in the understanding of concepts among the eighth-grade students of MTs Ma’arif between the class using the game-based learning method with smart jellyfish media and the class using the conventional method. This conclusion is supported by an N-gain score of 0.457. 2) There was a significant difference in the understanding of concepts among the eighth-grade students of MTs Ma’arif between the class using the game-based learning method with smart jellyfish media and the class using the conventional method. This conclusion is supported by the results of the independent sample t-test, which yielded a value of 2.032, indicating statistical significance at 0.05.